Effect of acute stressor on reproductive behavior differs between urban and rural birds. Issue 18 (20th August 2016) - Abolins‐Abols, Mikus; Hope, Sydney F.; Ketterson, Ellen D.
Abstract: The life‐history trade‐off between self‐maintenance and reproduction posits that investment in one function decreases investment in the other. Manipulating the costs and benefits of functions involved in a trade‐off may alter this interaction. Here we ask whether investment in self‐maintenance during a stress response alters territorial behavior in wild Dark‐eyed Juncos and whether rural and urban birds, which are known to differ in the magnitude of the stress response (greater in rural), also differ in the degree to which stress reduces territorial behavior. In rural and urban habitats, we measured territorial behavior using song playback, followed by either an acute stressor (capture and collection of a blood sample) or a nonstressful control situation. The following day, we again measured territorial behavior, predicting greater reduction in territorial behavior in individuals exposed to the stressor but a lesser reduction in territorial behavior in the urban as compared to the rural environment. We further assessed individual and population differences in response to stressors by measuring flight initiation distance, breath rate, and corticosterone levels in the blood. The rural population had a higher physiological and behavioral stress response than the urban population, and acute capture stress had a lasting (24 h) negative effect on territorial behavior, but only in the rural habitat. However, individual‐level differences in measures of the stress response did not explain variation in the impact of stress on territorial behavior. Our findings show that stressors can have a negative effect on territorial behavior, but that this effect may differ between populations that vary in their stress ecology. Abstract : We investigated whether acute stressor alters territorial behavior in wild dark‐eyed juncos and whether rural and urban birds, which are known to differ in the magnitude of the stress response, also differ in the degree to which stress reduces territorial behavior. The rural population had a higher physiological and behavioral stress response than the urban population, and acute capture stress had a lasting negative effect on territorial behavior, but only in the rural habitat. Our findings show that stressors can have a negative effect on territorial behavior, but that this effect may differ between populations that vary in their stress ecology.